Designing the recognition of Sn2+ ions and antioxidants: N-heterocyclic organosilatranes and their magnetic nanocomposites. (6th April 2020) - Singh, Gurjaspreet; Diksha,; Singh, Akshpreet; Sanchita,; Sharma, Geetika; Shilpy,; Pawan,; Espinosa-Ruíz, Cristóbal; Esteban, María Angeles
Abstract : The present work involves synthesis of new series of N-heterocyclic unsymmetrical organosilatranes and the synthesized compounds were explored for the detection of Sn 2+, cytotoxicity and antioxidant activity. Abstract : This article presents the design and synthesis of a new series of N-heterocyclic unsymmetrical organosilatranes starting from carboxaldehydes and [3-(2-aminoethylamino)propyl]trimethoxysilane. The molecular structures of the desired organosilatranes were confirmed by various characterization techniques such as elemental analysis, FTIR, NMR ( 1 H and 13 C) and mass spectroscopy. The prepared compounds were evaluated for their cationic chemosensing activities and the recognition studies show considerable variations in the intensity and λ max values of absorption and emission spectra on addition of Sn 2+ ions. Further immobilization of N-heterocyclic unsymmetrical organosilatranes was done on a magnetic silica surface and the resultant nanohybrids were identified by numerous analytical techniques viz., FTIR, TGA, XRD, SEM, VSM and BET. The comparative detection studies of the nanoparticles with silatranes showed better Sn 2+ ion binding ability. Moreover, the pharmacokinetic profile of the synthesized compounds was analysed using MOLINSPIRATION and ADMET software and it gave auspicious results that triggered the investigation of the cytotoxicity and total antioxidant activity (TAA) of these molecules.